2019
DOI: 10.1021/acsphotonics.9b00717
|View full text |Cite
|
Sign up to set email alerts
|

Optimal High Efficiency 3D Plasmonic Metasurface Elements Revealed by Lazy Ants

Abstract: Recent transmissive optical metamaterials that leverage a generalized form of Snell's law to induce an anomalous refraction of light have garnered considerable interest in both optical and materials communities. However, most of these designs have primarily centered around parametric studies of planar canonical structures for their low profile and relative ease of manufacturing. In many of these cases, all-dielectric designs are preferred over metallodielectrics due to their low loss characteristics. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Various devices have been recently optimized using GA or using some advanced evolutionary strategies as shown in refs. [53][54][55][56]61]. To highlight the basic concepts of the numerical optimization methods and mention briefly some possible applications, the readers can refer to recent review works about metasurfaces and nanophotonics (refs.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…Various devices have been recently optimized using GA or using some advanced evolutionary strategies as shown in refs. [53][54][55][56]61]. To highlight the basic concepts of the numerical optimization methods and mention briefly some possible applications, the readers can refer to recent review works about metasurfaces and nanophotonics (refs.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…[64] Recently, some advanced evolutionary strategies have also been extended to design multifunctional metasurfaces. [53,65,66] For the GA approaches presented here, all require fullwave calculations of Maxwell's equations for all devices in each generation, which adds up to at least a few thousand of simulations. Therefore, this technique is computationally expensive and has to be used with efficient fullwave solvers, especially when considering the optimization of 3D structures.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In the optical and IR regimes, these nanoantennas are usually limited to simple canonical shapes such as triangles, rectangles, rings, cylinders, and their combinations. However, it has been shown that nanoantennas based on unintuitive shapes (i.e., free-form geometries) can significantly outperform more traditional geometries in various metrics, such as maximum transmission or reflection magnitudes, phase coverage, field of view, and spectral bandwidth [283,284]. When paired with active materials, metasurfaces comprised of unintuitive nanoantenna shapes offer the potential to achieve major At .-μm wavelength with   cm − hole concentration.…”
Section: Advanced Design and Optimization: Toward Multifunctional Metmentioning
confidence: 99%